Clinical evaluation of a novel microfluidic device for epitope-independent enrichment of circulating tumour cells in patients with small cell lung cancer. Issue 2 (25th November 2015) - Chudziak, Jakub; Burt, Deborah J.; Mohan, Sumitra; Rothwell, Dominic G.; Mesquita, Bárbara; Antonello, Jenny; Dalby, Suzanne; Ayub, Mahmood; Priest, Lynsey; Carter, Louise; Krebs, Matthew G.; Blackhall, Fiona; et al.
Abstract : Evaluation of a novel microfluidic device for epitope-independent enrichment of circulating tumour cells using clinical samples from patients with SCLC. Abstract : Circulating tumour cells (CTCs) have potential utility as minimally-invasive biomarkers to aid cancer treatment decision making. However, many current CTC technologies enrich CTCs using specific surface epitopes that do not necessarily reflect CTC heterogeneity. Here we evaluated the epitope-independent Parsortix system which enriches CTCs based on size and rigidity using both healthy normal volunteer blood samples spiked with tumour cells and blood samples from patients with small cell lung cancer (SCLC). Blood samples were maintained unfractionated at room temperature for up to 4 days followed by plasma removal for circulating free DNA (cfDNA) isolation and direct application of the remaining cell component to the Parsortix system. For tumour cells expressing the EpCAM cell surface marker the numbers of spiked cells retained using the Parsortix system and by EpCAM-positive selection using CellSearch® were not significantly different, whereas only the Parsortix system showed strong enrichment of cells with undetectable EpCAM expression. In a pilot clinical study we banked both enriched CTCs as well as plasma from SCLC patient blood samples. Upon retrieval of the banked Parsortix cellular samples we could detect cytokeratin positive CTCs in all 12 SCLC patients tested. Interestingly, processing parallel samples from the same patients by EpCAM enrichment using CellSearch® revealed only 83% (10/12) with cytokeratin positive CTCs indicating the Parsortix system is enriching for EpCAM negative SCLC CTCs. Our combined results indicate the Parsortix system is a valuable tool for combined cfDNA isolation and CTC enrichment that enables CTC analysis to be extended beyond dependence on surface epitopes.